2015
DOI: 10.1097/md.0000000000001862
|View full text |Cite
|
Sign up to set email alerts
|

Broad-spectrum Antibiotic Plus Metronidazole May Not Prevent the Deterioration of Necrotizing Enterocolitis From Stage II to III in Full-term and Near-term Infants

Abstract: Necrotizing enterocolitis (NEC) is the most common and frequently dangerous neonatal gastrointestinal disease. Studies have shown broad-spectrum antibiotics plus anaerobic antimicrobial therapy did not prevent the deterioration of NEC among very low birth preterm infants. However, few studies about this therapy which focused on full-term and near-term infant with NEC has been reported. The aim of this study was to evaluate the effect of broad-spectrum antibiotic plus metronidazole in preventing the deteriorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 43 publications
0
25
1
Order By: Relevance
“…Recent studies assessed the effectiveness of broad spectrum antibiotics in conjunction with Metronidazole to prevent the deterioration of NEC from stage II to III in full term and near term infants. Studies show that infants with stage II NEC are more likely to progress onto stage III if they are short on colostrum feeding, require fresh frozen plasma or cryoprecipitate transfusions or have an elevated C-reactive protein [2,4]. Additionally, they found that the rate of deterioration from stage II NEC to stage III NEC did not vary significantly between the group of infants who were treated with Metronidazole and the group of those who were not, and that the mortality rates in both groups was similar [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies assessed the effectiveness of broad spectrum antibiotics in conjunction with Metronidazole to prevent the deterioration of NEC from stage II to III in full term and near term infants. Studies show that infants with stage II NEC are more likely to progress onto stage III if they are short on colostrum feeding, require fresh frozen plasma or cryoprecipitate transfusions or have an elevated C-reactive protein [2,4]. Additionally, they found that the rate of deterioration from stage II NEC to stage III NEC did not vary significantly between the group of infants who were treated with Metronidazole and the group of those who were not, and that the mortality rates in both groups was similar [2].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that infants with stage II NEC are more likely to progress onto stage III if they are short on colostrum feeding, require fresh frozen plasma or cryoprecipitate transfusions or have an elevated C-reactive protein [2,4]. Additionally, they found that the rate of deterioration from stage II NEC to stage III NEC did not vary significantly between the group of infants who were treated with Metronidazole and the group of those who were not, and that the mortality rates in both groups was similar [2]. Therefore, these studies suggest that broad spectrum antibiotics administered along with Metronidazole may not prevent deterioration from stage II to stage III in full-term and near term infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Broad-spectrum antibiotics have not been shown to decrease the progression of NEC. 32 Autmizguine et al 33 compared NEC treatment with anaerobic coverage in low-birthweight infants in 348 NICUs across the United States. In patients with medical NEC, there was no difference in death or intestinal strictures, in fact, there was an increase in intestinal strictures in infants who received anaerobic antimicrobial therapy.…”
Section: Necrotizing Enterocolitismentioning
confidence: 99%
“…In the article “Broad-spectrum Antibiotic Plus Metronidazole May Not Prevent the Deterioration of Necrotizing Enterocolitis From Stage II to III in Full-term and Near-term Infants: A Propensity Score-matched Cohort Study”, 1 which appeared in Volume 94, Issue 42 of Medicine , the affiliations were incorrectly given in the original article. The article has since been corrected online.…”
mentioning
confidence: 99%